Linking health education, civic engagement, and research at a large Federally Qualified Health Center to address health disparities. (4th March 2022) - Chinchilla, Melissa; Montiel, Gloria Itzel; Jolles, Monica Perez; Lomeli, Matthew Charles; Wong, Carolyn F.; Escaron, Anne Laure; González‐Figueroa, Evelyn; Garcia, Joanna; Valencia, Aisli Briceida; Kadono, Mika; Acosta, Arturo; Martinez, Corina; et al.
Abstract: Objective: To develop a framework for patient‐centered research in a community health center. Study setting: Primary organizational case‐study data were collected at a large Federally Qualified Health Center (FQHC) in Southern California from 2019 to 2021. Study design: Thirty stakeholders, including patients, community leaders, students, medical providers, and academic partners, participated in community‐engagement capacity‐building exercises and planning. These activities were guided by Community Based Participatory Principles and were part of an initiative to address health disparities by supporting patient and community‐engaged research. Data collection: The study included an iterative development process. Stakeholders participated in a total of 44 workgroup meetings and 7 full‐group quarterly convenings. The minutes of the meetings from both workgroups and quarterly convenings were used to document the evolution of the initiative. Principle findings: Stakeholders concluded that health equity research needs to be part of a larger engagement ecosystem and that, in some ways, engagement on research projects may be a later‐stage form of engagement following patient/community and staff/researcher coeducation and cocapacity building efforts. Conclusions: Community health center stakeholders viewed successful engagement of community members in patient‐centered health equity research as involving a web of longitudinal, evolving internal and external relationships rather than discrete, time‐limited, and single‐project‐based dyadic connections.